Dense Planting with Reducing Nitrogen Rate Increased Nitrogen Use Efficiency and Translocated Nitrogen in Grains in Double-Cropped Rice - Zhuo Luo; Haixing Song; Min Huang; Zhenhua Zhang; Zhi Peng; Zhichang Yang; Tao Shen; Gongwen Luo (Agronomy, 2022)
Nitrogen fertilization and planting density are two key factors that influence the yield of rice. Reducing nitrogen fertilizer input and increasing planting density will help to improve nitrogen use efficiency and stabilize yield. Field and 15N tracer method in plot experiments were conducted to study the trends of yield, nitrogen use efficiency (NUE) and nitrogen transfer of hybrid rice and conventional rice under dense planting with a reduced nitrogen rate (DPRN) and sparse planting with a high nitrogen rate (SPHN). Among the nitrogen in rice plants, the proportion of nitrogen from fertilizer under the DPRN was reduced by 1.8–13%. The late-season rice (LSR) had a higher rate of decrease compared with the early-season rice (ESR). The uptake efficiency of nitrogen fertilizer was significantly higher under the DPRN than that under the SPHN, with an increase of 7.7–21.9%. The accumulated nitrogen and translocated ratio under the DPRN before the heading stage were 6.1–10.8% and 2.0–9.6% higher than those under the SPHN, respectively. The yield did not change under different treatments. Those findings suggest that the DPRN could guarantee a stabilized yield while increasing the NUE and the amount of translocated nitrogen in the double-cropped rice system.